2023
DOI: 10.21608/erurj.2023.210583.1024
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and biological diversity of genus Ludwigia: A comprehensive review

Abstract: Onagraceae is common as willowherb or evening primrose family which is divided into two subfamilies; Ludwigioideae (mainly Ludwigia genus) and Onagroideae. Genus Ludwigia belonging to the family Onagraceae is an important aquatic plant-including genus and characterized by its myriad traditional uses as treatment of hormonal imbalances, urinary complaints, promoting prostate health, and antimicrobial potential. This review focuses on the secondary metabolites and biological significance of various Ludwigia spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…f. specie belongs to lamiaceae family and were used to treat Snake bite antidote, and epilepsy, also Lamiaceae are good in terms of herbal medicine because they has antifungal, and have antibacterial action, traditionally were used to cure scorpion bites [4]. Also Shawky et al [52] reported Ludwigia spp. has several health benefits and biological activities, Ludwigia were used as anti-inflammatory, anti-diabetic, and antimicrobial properties.…”
Section: Lamiaceae Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…f. specie belongs to lamiaceae family and were used to treat Snake bite antidote, and epilepsy, also Lamiaceae are good in terms of herbal medicine because they has antifungal, and have antibacterial action, traditionally were used to cure scorpion bites [4]. Also Shawky et al [52] reported Ludwigia spp. has several health benefits and biological activities, Ludwigia were used as anti-inflammatory, anti-diabetic, and antimicrobial properties.…”
Section: Lamiaceae Sppmentioning
confidence: 99%
“…Onagraceae is an important aquatic plant-including genus and characterized by its myriad traditional uses as treatment of hormonal imbalances, urinary complaints, promoting prostate health, and antimicrobial potential [52].…”
Section: Onagraceaementioning
confidence: 99%